The Extent to Which Indicators of Competitive Advantage Are Achieved in Small and Medium Enterprises On the Syrian Coast "Empirical Study" - علي يونس ميّا,; سومر ناصر ,; يارا حكمت عيسى, (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to verify the extent to which small and medium enterprises in the Syrian coast apply the indicators of competitive advantage, represented by: cost, quality, creativity, time, and response. The research relied on the descriptive approach, and the study population included all managers or owners of small and medium enterprises in the Syrian coast, where the researcher drew a random sample of managers or owners of these projects, The sample size reached (113) project managers or owners, divided between service projects, industrial projects and tourism projects. The results showed that the small and medium enterprises under study apply to a large extent the indicators of competitive advantage, with a relative importance (73.04%). This is reflected in the competitive advantage indicators (cost, quality, creativity, time, response) represented in the success of the project by exploiting its available resources to improve its performance efficiently and effectively in a way that leads to its success and continued growth.